Study of Nepal’s Economic Relations with China - Prasad, Uma Shankar (Journal of Development and Administrative Studies, 2016)
Nepal has a very long historical, political, cultural and economic cooperation with China. According to the International Monetary Fund (IMF), China is the country having the world’s largest economy in 2014 for purchasing power parity with 17.632 trillion US dollar and second largest economy for nominal GDP. Being one of the rising Asian powers, China wants to achieve the status of global power. In this perspective, it is needed for China to win the trust of neighboring countries. China has already announced that it will pay more attention and reinforce its cooperation with its neighbors. Being a China’s good neighbor, Nepal naturally wants to see China as a global power in coming years. This article analyzes some facets of Nepal’s long economic relation with China. The paper concludes that although the political and economic relation between Nepal and China has very long history, the relation has not been able to enhance various economic indicators like trade, investment, tourism etc. and therefore it is needed to focus on economic endeavors between these two countries in coming days. The Journal of Development and Administrative Studies (JODAS) Vol. 23(1-2), pp. 23-32